Compressibilidade de um solo sob sistemas de pastejo rotacionado intensivo irrigado e não irrigado - Lima, C. L. R. (2004)
Increment in pasture productivity has been associated with the understanding of the soil behavior under compression. The objective of this research was to quantify (a) the compression curves and (b) the preconsolidation pressure of the soils under non-irrigated and irrigated short duration grazing systems. Ninety-six undisturbed soil samples were taken from the four successive pasture cycles of Tanzania grass (Panicum maximum Jacq.) in a Hapludalf. The samples were saturated in water and equilibrated at the matrix potential (y): -10 kPa and then were weighed and submitted to an uniaxial compression test, applying the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. in a Hapludalf. The samples were saturated in water and equilibrated at the matrix potential (y): -10 kPa and then were weighed and submitted to an uniaxial compression test, applying the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. Panicum maximum Jacq.) in a Hapludalf. The samples were saturated in water and equilibrated at the matrix potential (y): -10 kPa and then were weighed and submitted to an uniaxial compression test, applying the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system. y): -10 kPa and then were weighed and submitted to an uniaxial compression test, applying the following pressures: 25, 50, 100, 200, 400, 600, 800, 1,000, 1,300, and 1,600 kPa. Results support the hypothesis that there is a difference between the soil compressibility under nonirrigated and irrigated short-duration grazing systems. The higher initial compaction verified in irrigated short-duration grazing system favored the displacement of the uniaxial compression curves for higher bulk density values. The preconsolidation pressure was significantly higher in the fourth pasture cycle under irrigated than under the non-irrigated short duration grazing system.